Developing an Efficient Oil Extraction Process Using Soxhlet Extractor to Improve Oil Yield of Turmeric Rhizomes in Southern Kaduna (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract : The inefficiency often observed in oil extraction methods can be attributed to insufficient kinetic and thermodynamic data during the design phase. This study aimed to optimize the turmeric oil extraction process using 250 ml of n-hexane and 50 g of turmeric sample from Southern Kaduna. Six kinetic models and thermodynamic principles were applied to describe the extraction process. The physicochemical properties of the turmeric oil were analyzed following the methods recommended by the Association of Official Analytical Chemists. The results showed that the optimal conditions for turmeric oil extraction were temperature range of 343 to 353 K, an extraction time of 5 to 6 hours and a solvent-to-sample ratio of 1:5. The extraction followed pseudo-second-order kinetics, with an activation energy (Ea) of 18.8327 kj/molK. Thermodynamic analysis revealed an enthalpy change (∆H) of 19.6389 kj/mol, an entropy change (∆S) of 0.08710 kj/molK and positive Gibbs’ free energy change (∆G) at all tested temperatures. These thermodynamic results suggest that the extraction process is endothermic, requiring continuous energy input, exhibits high randomness and is non-spontaneous. Furthermore, the physicochemical analysis confirmed that the oil is safe for consumption and suitable for use in soap production, cosmetics and pharmaceuticals.